2021
DOI: 10.1093/crocol/otab039
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab Experience in Children and Adolescents With Inflammatory Bowel Disease: A Multicenter Observational Study

Abstract: Background Vedolizumab is increasingly used off-label to treat children and adolescents with inflammatory bowel disease (IBD). In the absence of rigorous clinical trial experience, multicenter observational data are important to establish expectations for efficacy and safety. We examined one-year outcomes following vedolizumab therapy in a large multicenter paediatric IBD cohort. Methods We performed a retrospective study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Of these, thirty-eight were excluded for various reasons (Fig. 1 ), leaving 10 articles including a total of 455 patients ( n = 216 CD, n = 239 UC/IBD-U) [ 22 31 ]. All studies focused on both CD and UC/IBD-U.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, thirty-eight were excluded for various reasons (Fig. 1 ), leaving 10 articles including a total of 455 patients ( n = 216 CD, n = 239 UC/IBD-U) [ 22 31 ]. All studies focused on both CD and UC/IBD-U.…”
Section: Resultsmentioning
confidence: 99%
“…All studies focused on both CD and UC/IBD-U. Seven studies reported clinical remission rates [ 22 25 , 29 31 ]. Four studies reported clinical response rates [ 23 , 25 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations